Design and Simulation of Globoidal Cam Indexing Mechanism for Rotary Concave Die of Cold Heading Machine - Liu Yangxu; Luo Shanming; Chang Xuefeng (Jixie chuandong)
The mathematical model of the globoidal cam indexing mechanism applied to the rotary concave die of cold heading machine is established. The parameters of the globoidal cam indexing machine are designed and the motion law of globoidal cam is selected based on the operation condition of the cold heading machine.Through detailed cases,the parametric model of globoidal cam indexing mechanism is realized by using the Pro /E and Matlab,the dynamics model of it is developed by using the ADAMS and the motion simulations are carried out. The research shows that,under high- speed condition,the globoidal cam indexing mechanism has the characteristics of stable meshing and the locating accuracy reaches 36″ applied to the cold heading machine.